Impacts of Earthquake and Earthquake-induced Disasters on Community Forests in Nepal - Dhamala, Man Kumar; Aryal, Prakash Chandra; Bhandari, Bikash; Kharel, Kailash; Khadka, Dipak (Journal of Environment Sciences, 2023)
Managing the commons is a challenging issue during crisis such as earthquakes. We considered four community forests, two from Gorkha and one from each of Dolakha and Sindupalchowk districts that were major earthquake affected areas. The study made use of ecological and socioeconomic survey techniques to assess the impacts of earthquake on community forests and management status of those forests. We calculated density of seedling, sapling and tree species and diameter size distribution of trees. We also analysed the forest status changes before and after the earthquake events and distribution of timber and fire wood in the community forest user groups. Seedling, sapling and adult trees number wise regeneration status of trees was good in all the studied forest whereas DBH size class diagram were bell shaped indicating unsustainable regeneration. Most of the respondents reported poor forest management after the earthquake and wood distribution has drastically increased after the earthquake 2015. From this study it is recommended that community forest management practices should be resilient to disasters and prepare alternative solutions to lower the pressure on forest products so as to maintain sustainable regeneration of forest trees and regular supplies of resources in future.